Transition-metal catalysed C–N bond activation. (14th January 2016) - Wang, Quanjun; Su, Yijin; Li, Lixin; Huang, Hanmin
Abstract : Efficient strategies for transition-metal catalyzed C–N bond activation and their applications in new C–X bond formation reactions are summarized. Abstract : Transition-metal catalysed C–N bond activation has attracted much attention and become one of the most promising bond disconnection and formation strategies that encompass a broad spectrum of applications in many reactions. In this tutorial review, efficient strategies for catalytic cleavage of C(sp)–N, C(sp 2 )–N and C(sp 3 )–N bonds and their applications in new C–C and C–N bond formation reactions are summarized.